Discretion and contextual influences on creative thinking - Tadik, Harun; Runco, Mark A.; Bahar, Kadir (Frontiers in Psychology, 2025)
This investigation used a new method to measure the role of discretion in the creative process. In this context, discretion refers to a particular kind of awareness, and more specifically to an individual's intentional engagement in the creative process. In this investigation, discretion was operationalized as decisions about whether or not to express creative ideas in different social contexts. Discretion may lead an individual to express many creative ideas in one setting but fewer or no creative ideas in a different setting. Two sets of divergent thinking and idea preference measures were adapted from previous research and used to assess creative potential, along with self-reports of ideation, Big Five personality traits, and creative attitudes and values. The divergent thinking tasks were presented with instructions that suggested different social contexts. One context was relaxed and playful conditions, which previous research has shown to support originality. The other instructions described a work environment where there was pressure to succeed and an emphasis on correct ideas. Statistical analyses confirmed differences between the two conditions, suggesting that individuals exercised discretion when they generated ideas. Correlational and hierarchical regression analyses indicated that openness to experience, education, and creative potential were significantly related to discretion. Practical implications and suggestions for future research are discussed.